SQUID PRODUCTION ON INCOME AND POVERTY LEVEL OF FISHERMEN'S HOUSEHOLDS IN PESAWARAN REGENCY, LAMPUNG PROVINCE - Maya Riantini (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Squid (Loligo spp.) contains a high nutritional value and is a fishery resource that can be used as an economic source so that the catch fishery products can be utilized by fishermen to support their household needs. The aim of this study was to determine the relationship between squid fishing and the income and poverty level of fishermen's households. This study was conducted in Sukajaya Lempasing Village, Teluk Pandan District, Pesawaran Regency, Lampung. This study used questionnaires and interviews with 20 respondents of squid fishermen. The results showed that fishermen's education was 75% at the elementary level, and fishermen became the main occupation by 55%. The income of squid fishermen had differences in the catch period, namely the catch of season 1 (2,148,092 IDR) and season 2 (1,352,992 IDR). Based on the BPS category 80% of fishing families are classified as poor, according to the World Bank 90 % during squid season and 100% during the non-squid season are in the category of poor, and according to ADB 50% is classified as poor and 90% is poor during the squid season and not the squid season. Because of these differences, it is necessary to manage local resources to reduce poverty by increasing the awareness of squid fishermen in financial management, supported by increasing local government capacity, and revitalizing local institutions.